Improving The Methodology For The Development Of Mediacompetency Of Students Of Higher Educational Institutions (On The Example Of The Educational Science” Informatics And Digital Technologies") (Progress Annals: Journal of Progressive Research, 2024)
this article highlights the improvement of the methodology for the development of mediacompetency of students of higher education institutions.